Legal Protection Of International Business Transactions On Electronic Commerce (Ecommerce) Transaction Contracts - Putri, Allya Maulida; Iskandar, Hardian (Jurnal Justiciabelen, 2023)
Along with the demand for international trade which is quite a lot, the technology and means of electronic communication are also developing. E-commerce is an electronic transaction that is very supportive in the economic field, especially international business transactions. International business transactions are a civil law study that provides greater opportunities for each party to make, agree on, and implement the contents of the agreements they make. With various technological advances, the world provides opportunities for the international community to establish relations between them. In line with these advantages, it is possible that there will still be deficiencies which will cause disputes between the contract makers. These problems can arise because of differences between them, such as in terms of culture, legal perspective, and so on. Therefore, parties from different countries must understand the contracts they make and pay attention to the laws in force in other countries before entering into certain contracts. To prevent unwanted legal consequences, a clear understanding of legal protection is required. This research method is a legal normative research with a statutory approach.